'More jobs for TVET grads' - Fazleena, Aziz (The New Straits Times Press, 2016)
It was a bittersweet moment for retired civil servant Noriyah Abd Manan, 60, from Lumut, Perak, when she received the certificate for her late son, Mohd Shafie Faiz.